Rotation of shoulder and hip axes during a basketball jump shot - Štirn, I.; Podmenik, N.; Supej, M.; Erculj, F. (International Journal of Performance Analysis in Sport, 2019)
The aim of our research was to determine the changes in rotation of the shoulder and hip axes in the transverse plane during the execution of a jump shot due to changing shooting distance. Fourteen youth national team basketball players, all shooting guards (age 15.43 ± 0.51 years) were tested. The analysis included 370 field goals, performed from three different distances (3.75 m, 5.25 m and 6.75 m). We used the inertial suit for data acquisition. Results showed that differences in shoulder and hip rotation axes angles occurred at the very beginning of the shooting action and that these differences were preserved until landing. Differences in shoulder and hip rotation measured during the shots from different distances were obtained showing the greatest rotation in all phases of the shot when shooting from the longest distance. While the rotation in the shoulder axis finished in the moment of release, in the hip axis it was still increasing due to inertia until the moment of landing. This shows how the shooter locks the shoulder position to align the upper body for the most accurate shot.